The genome of cowpea (Vigna unguiculata [L.] Walp.). (28th May 2019) - Lonardi, Stefano; Muñoz‐Amatriaín, María; Liang, Qihua; Shu, Shengqiang; Wanamaker, Steve I.; Lo, Sassoum; Tanskanen, Jaakko; Schulman, Alan H.; Zhu, Tingting; Luo, Ming‐Cheng; Alhakami, Hind; Ounit, Rachid; et al.
Summary: Cowpea ( Vigna unguiculata [L.] Walp.) is a major crop for worldwide food and nutritional security, especially in sub‐Saharan Africa, that is resilient to hot and drought‐prone environments. An assembly of the single‐haplotype inbred genome of cowpea IT97K‐499‐35 was developed by exploiting the synergies between single‐molecule real‐time sequencing, optical and genetic mapping, and an assembly reconciliation algorithm. A total of 519 Mb is included in the assembled sequences. Nearly half of the assembled sequence is composed of repetitive elements, which are enriched within recombination‐poor pericentromeric regions. A comparative analysis of these elements suggests that genome size differences between Vigna species are mainly attributable to changes in the amount of Gypsy retrotransposons. Conversely, genes are more abundant in more distal, high‐recombination regions of the chromosomes; there appears to be more duplication of genes within the NBS‐LRR and the SAUR‐like auxin superfamilies compared with other warm‐season legumes that have been sequenced. A surprising outcome is the identification of an inversion of 4.2 Mb among landraces and cultivars, which includes a gene that has been associated in other plants with interactions with the parasitic weed Striga gesnerioides . The genome sequence facilitated the identification of a putative syntelog for multiple organ gigantism in legumes. A revised numbering system has been adopted for cowpea chromosomes based on synteny with common bean ( Phaseolus vulgaris ). An estimate of nuclear genome size of 640.6 Mbp based on cytometry is presented. Significance Statement: State‐of‐the‐art technologies and assembly methods were used to generate a reference genome sequence of cowpea, a drought‐resilient crop on which millions of people in sub‐Saharan Africa depend as a source of protein. This sequence facilitated the identification of: repetitive elements and gene families expanded in cowpea compared with other closely related legumes; a large and apparently rare chromosomal inversion; and an interesting candidate gene that is associated with several domestication‐related traits.